Strengthening e-Government through SIMPEG: Digital Transformation of Civil Servant Mutation in Badung Regency - Dionisia, Inda Putri; Wijaya, Komang Adi Sastra (Universitas Padjadjaran, 2025)
The Human Resources Management Information System (SIMPEG), which is based on e-Government, has accelerated the transformation of personnel administration into digital thanks to advancements in information technology. This study investigates how SIMPEG enhances e-Government by transforming the civil servant mutation process in Badung Regency, Bali Province, Indonesia. This transformation resulted from the previous inefficient manual system, which often led to delays, inaccuracies, and lack of clarity. Data was collected thru semi-structured interviews with structural officials, system operators, and technical staff at the Personnel and Human Resource Development Agency (BKPSDM), supported by documentation and direct observation. A qualitative case study approach was used. This research involved ten informants who were purposively selected based on consent and anonymity. The research results show that SIMPEG reduces errors, ensures accurate and real-time data, and speeds up the mutation process. An integrated data system improves verification, inter-unit coordination, and administrative transparency. More than just a technical improvement, SIMPEG helps realize e-Government principles such as efficiency, accountability, and transparency in local governance. This research shows that SIMPEG is not only a digital tool, but also an important part of e-Government reform at the local level. This research shows that the use of technology can modernize personnel management and support sustainable bureaucratic transformation.